2020
DOI: 10.1002/cbin.11416
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of DNA‐binding protein A enhances the chemotherapy sensitivity of colorectal cancer via suppressing the Wnt/β‐catenin/Chk1 pathway

Abstract: DNA‐binding protein A (dbpA) is reported to be upregulated in many cancers and associated with tumor progress. The present study aimed to investigate the role of dbpA in 5‐fluorouracil (5‐FU)‐resistant and oxaliplatin (L‐OHP)‐resistant colorectal cancer (CRC) cells. We found that 5‐FU and L‐OPH treatment promoted the expression of dbpA. Enhanced dbpA promoted the drug resistance of SW620 cells to 5‐FU and L‐OHP. DbpA knockdown inhibited cell proliferation, induced cell apoptosis, and cell cycle arrested in SW6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…5 - FU-resistant SW620 cells (SW620-R) were generated by continuously exposing the cells to an increasing concentration gradient of 5-FU (#F6627, 10–200 μM, Sigma-Aldrich) and cultured in Dulbecco’s Modified Eagle’s Medium (DMEM, # 12800017, Invitrogen, Carlsbad, CA, USA) containing 10% fetal bovine serum (FBS, #26400044, Invitrogen, USA), 1% penicillin/streptomycin ( # 15070063, Gibco, BRL) at 37℃ in a humidified incubator with 5% CO2 based on the recent report in 2020 [ 32 ]. 5-FU-resistant HCT116 cells (HCT116-R) were established by treating them with gradually increasing concentrations of 5-FU (#F6627, 5 μM to 50 μM, Sigma-Aldrich) for 9 months and were maintained in Iscove’s modified Dulbecco’s medium (IMDM, # 12440–053, Invitrogen, Carlsbad, CA, USA) with 10% FBS (#26400044, Invitrogen, USA) and 1% penicillin and streptomycin ( # 15070063, Gibco, BRL), in a humidified incubator (5% CO2) at 37℃, as previously described [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…5 - FU-resistant SW620 cells (SW620-R) were generated by continuously exposing the cells to an increasing concentration gradient of 5-FU (#F6627, 10–200 μM, Sigma-Aldrich) and cultured in Dulbecco’s Modified Eagle’s Medium (DMEM, # 12800017, Invitrogen, Carlsbad, CA, USA) containing 10% fetal bovine serum (FBS, #26400044, Invitrogen, USA), 1% penicillin/streptomycin ( # 15070063, Gibco, BRL) at 37℃ in a humidified incubator with 5% CO2 based on the recent report in 2020 [ 32 ]. 5-FU-resistant HCT116 cells (HCT116-R) were established by treating them with gradually increasing concentrations of 5-FU (#F6627, 5 μM to 50 μM, Sigma-Aldrich) for 9 months and were maintained in Iscove’s modified Dulbecco’s medium (IMDM, # 12440–053, Invitrogen, Carlsbad, CA, USA) with 10% FBS (#26400044, Invitrogen, USA) and 1% penicillin and streptomycin ( # 15070063, Gibco, BRL), in a humidified incubator (5% CO2) at 37℃, as previously described [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another research has found DNA-binding protein A (dbpA) may be a new and effective therapeutic target, which is useful for colorectal cancer (CRC). The downregulation of dbpA is a pivotal method to inhibit cell proliferation and induce cell apoptosis as well as cell cycle arrest in cancer cells because it can not only restrict the growth of tumor but also improve the drug sensitivity of CRC cells in vivo ( Tong et al, 2020 ). These studies have shown that DNA-binding proteins exist in living cells widely and participate in many cell activities.…”
Section: Introductionmentioning
confidence: 99%